Resistant Hypertension in Chronic Kidney Disease - Covic, Adrian; Kanbay, Mehmet; Lerma, Edgar V. (Springer International Publishing : Imprint: Springer, 2017)
This comprehensive volume provides a detailed review on the general work up of chronic kidney disease-associated resistant hypertension. This title is separated into four parts; the first of which provides definitions, epidemiology, characteristics, risk stratification and outcomes of resistant and apparent treatment resistant hypertension. The next two sections explore pathophysiology and diagnosis, treatment in the light of new guidelines, as well as procedures and devices for neural modulation. Part four discusses public health approaches to resistant hypertension, educational programs, and resistant hypertension for general practitioners. Resistant Hypertension in CKD brings up-to-date information to nephrologists, internists, cardiologists and a wide array of other clinicians and health professionals taking care of chronic kidney disease patients.
Keywords: Medicine.; Cardiology.; Nephrology.; elektronické knihy; electronic books